Implementasi Program Peningkatan Ketahanan Pangan (Studi pada Dinas Pertanian Kabupaten Blitar) - Alfia, Lutfi (FIA UB, 2016)
Food security is still a problem that is difficult to be solved. This paper discusses the efforts of the Department of Agriculture of Blitar Regency to achieve food security through the Food Security Enhancement Program. The study was conducted using descriptive qualitative approach using the policy implementation theory by M.S.Grindle. The results showed that in terms of both policy content and context of implementation supports the implementation of the Food Security Enhancement Program conveniently. But the successful of the implementation of this program only support food security in the aspect of availability alone. This means that in order to achieve intact food security, it can not only be done in terms of availability alone but it needed the development synergy of the three subsystem of food security, namely availability, access and utilization of food.